2020
DOI: 10.1111/bcp.14406
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic index of inhaled corticosteroids in asthma: A dose–response comparison on airway hyperresponsiveness and adrenal axis suppression

Abstract: Aims To compare the airway potency, systemic activity and therapeutic index of three inhaled corticosteroids that differ in glucocorticoid receptor binding affinity, physicochemical and pharmacokinetic properties. Methods This escalating‐dose, placebo‐controlled, cross‐over study randomised adults with asthma to 1 or 2 treatment periods with ≥25 days washout in‐between. Each treatment period comprised five 7‐day dose escalations (μg/d): fluticasone furoate (FF; 25 → 100 → 200 → 400 → 800), fluticasone propiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 28 publications
(94 reference statements)
4
57
0
4
Order By: Relevance
“…In contrast, a pharmacological study concluded that ICS molecules are not therapeutically similar: across the approved doses for asthma, fluticasone furoate (FF) gave more protection against airway hyperresponsiveness with less systemic activity (measured via 24-hour plasma cortisol suppression), and had a wider therapeutic index (systemic activity/airway potency ratio), than FP or budesonide. 61 On the other hand, when we look at GINA steps 3 to 5, we can see that ICS/formoterol is preferred over SABA as rescue medication. However, this might be a problem in patients who are receiving other combinations such as FF/ vilanterol because we don't have any experience in using two different combinations simultaneously in the same patient.…”
Section: Moderate To Severe Asthmamentioning
confidence: 99%
“…In contrast, a pharmacological study concluded that ICS molecules are not therapeutically similar: across the approved doses for asthma, fluticasone furoate (FF) gave more protection against airway hyperresponsiveness with less systemic activity (measured via 24-hour plasma cortisol suppression), and had a wider therapeutic index (systemic activity/airway potency ratio), than FP or budesonide. 61 On the other hand, when we look at GINA steps 3 to 5, we can see that ICS/formoterol is preferred over SABA as rescue medication. However, this might be a problem in patients who are receiving other combinations such as FF/ vilanterol because we don't have any experience in using two different combinations simultaneously in the same patient.…”
Section: Moderate To Severe Asthmamentioning
confidence: 99%
“…We read with interest the study by Daley-Yates et al 1 given that we already know that FF suppresses an ICS responsive type 2 biomarker, namely fractional exhaled nitric oxide (FeNO), for 18 days after cessation. 4 This in turn would result in an appreciable carryover effect of FF between weekly dose escalation which would not be seen with BUD as this has much shorter lung retention, and would further confound meaningful interpretation of any doseresponse effect.…”
Section: To the Editormentioning
confidence: 99%
“…We read with interest the study by Daley-Yates et al 1 which evaluated the relative therapeutic index of budesonide (BUD), fluticasone propionate (FP) and fluticasone furoate (FP) in asthma patients. We believe there are several inherent flaws with the design methodology of the trial which limit the clinical validity of the results.…”
Section: To the Editormentioning
confidence: 99%
“…Only one AMP challenge study reported a significant DR with FP in a recent incomplete crossover, 2‐period, dose‐escalation trial. 26 The FP dose‐escalation arm involved sequential doses: 50, 200, 500, 1,000, and 2,000 mcg/d. The dose‐shifts were 0, 0.4, 1.1, 1.7, and 2.3, respectively.…”
Section: Knowledge To Datementioning
confidence: 99%
“…One AMP challenge study included a fluticasone furoate (FF) dose‐escalation arm at sequential doses of 25, 100, 200, 400, and 800 mcg/d 26 . Dose‐shifts in AMP PC 20 from baseline were 1.1, 2.4, 2.9, 3.3, and 3.5, respectively, which suggests that the DR develops a plateau.…”
Section: Knowledge To Datementioning
confidence: 99%